Curcumin minimises histopathological and immunological progression in the ankle joints of collagen-induced arthritis rats - Kevin TTM,; Nur Idanis AS,; Anastasha B,; Mohd Faris MR,; Faizah Othman,; Taty Anna Kamarudin, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2020)
Curcumin is a traditionally used spice with a potential to treat various inflammatory diseases including arthritis. This study was aimed at observing curcumin’s effects on the histopathological progression and interleukin-1β (IL-1β) levels in collageninduced arthritis (CIA). Thirty male Sprague-Dawley rats (150+50 g) were divided into five random groups. A group was assigned as the normal control (CTRL), while the remaining were subcutaneously immunised with 150 µg of collagen emulsion on day 0. CTRL and CIA-Curcumin-d0 groups were supplemented daily with olive oil (1 ml/kg) and curcumin (110 mg/ml/kg) from day 0, respectively. The CIA-OV (negative control), CIA-Beta and CIA-Curcumin-d14 groups were given daily supplementation of olive oil (1 ml/kg), Betamethasone (0.5 mg/ml/kg), and curcumin (110 mg/ml/kg) from day 14, respectively. The daily oral supplementations continued until day 42. The study showed that CIA-Beta (**P<0.05) and CIACurcumin-d0 (**P=0.01) groups had significantly lower mean histological scores compared to CIA-OV, respectively. Serum IL-1β levels for CIA-Beta and CIACurcumin-d0 were not significantly raised on day 42 as to compared to day 0, and the mean increment of IL-1β levels from day 0 to day 42 were significantly lower (**P≤0.01) for all the CIA groups compared to CIA-OV. There was no significant difference in both mean histological scores and IL-1β levels of CIA-Curcumin-d0 compared to CIA-Beta. Early supplementation of curcumin could potentially minimise disease progression of CIA in rats.